Analisis Dampak Sistem Sosial Ekonomi pada Masyarakat Sekitar Perusahaan Tambang Batubara: Studi Kasus PT XYZ Desa Taman Dewa Kecamatan Mandiangin Kabupaten Sarolangun - Asnawati Asnawati; Suhar Suhar; Maulana Hamzah (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Mining plays an important role in humanitarian development and is a major economic asset for several countries. Mining exploitation, especially minerals, contributes significantly to economic growth and development in most countries.The impact can be positive or negative depending on the object affected. Mining generally has both positive and negative impacts on local communities. Companies engaged in mining can contribute to the development of socio-economic infrastructure such as roads, hospitals, schools and housing. While the income derived from mining activities contributes positively to the community's economy, mining activities serve as the main source of employment for local communities, and trigger the establishment of various small businesses such as catering, transportation and cleaning services.Themain data in qualitative research is words and actions, the rest is additional data such as documents and others. Data sources in this study consist of people, situations/events, and documentation.The mining industry in post-operation also leaves mine pits and acid mine water. Former coal mining pits have the potential to cause environmental impacts related to water quality and quantity. Not to mention the difficulty of getting clean water due to the drought of wells around the company. The drought of the well water was caused by extensive excavation of open land to extract coal. The vast land left over from the excavation became like a lake and the abandoned open land was no longer cultivated by the company, therefore the residents' wells experienced drought because the former excavated land became a lake.